2005
DOI: 10.1007/s11173-005-0055-9
|View full text |Cite
|
Sign up to set email alerts
|

Stabilities of Scandium(III)- and Yttrium(III)-Tiron Chelates and their hydrolytic behavior

Abstract: The interactions of Sc 3+ and Y 3+ ions with disodium 1,2-dihydroxybenzene-3,5-disulfonate (Na 2 H 2 L, where H 2 L 2-= Tiron) were investigated in aqueous solution by means of potentiometric and spectroscopic methods. The coordination of Tiron to Sc 3+ and Y 3+ takes place through two phenolic oxygen atoms of catecholate ion in different stoichiometries. Thus, the binding of Tiron to Sc 3+ occurs either in 1 : 1 or 1 : 2 molar ratios; they have resulted by the formation of [ ScL ] -and [ScL 2 ] 5-type complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In our previous studies, it was reported that the Y(III) ion forms stable complexes with a ligand where oxygen is the donor. In one of the said studies, interaction of disodium 1,2-dihydroxybenzene-3,5-disulfonate (Tiron), a catechole derivate, with the Y(III) ion was examined in I = 0.1 M NaClO 4 at 298.15 K. The number of protons decomposed in a 1:1 molar Y(III)−Tiron solution was found to be two per metal ion, and the stability constant of the ML complex was found to be log β 1 = 14.11 . As the constant was always found to be 3 for higher molar ratios, the stability constant was found to be log β 2 = 43.97 considering the presence of the M 2 L 3 dinuclear complex in the medium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous studies, it was reported that the Y(III) ion forms stable complexes with a ligand where oxygen is the donor. In one of the said studies, interaction of disodium 1,2-dihydroxybenzene-3,5-disulfonate (Tiron), a catechole derivate, with the Y(III) ion was examined in I = 0.1 M NaClO 4 at 298.15 K. The number of protons decomposed in a 1:1 molar Y(III)−Tiron solution was found to be two per metal ion, and the stability constant of the ML complex was found to be log β 1 = 14.11 . As the constant was always found to be 3 for higher molar ratios, the stability constant was found to be log β 2 = 43.97 considering the presence of the M 2 L 3 dinuclear complex in the medium.…”
Section: Resultsmentioning
confidence: 99%
“…In one of the said studies, interaction of disodium 1,2-dihydroxybenzene-3,5-disulfonate (Tiron), a catechole derivate, with the Y(III) ion was examined in I ) 0.1 M NaClO 4 at 298.15 K. The number of protons decomposed in a 1:1 molar Y(III)-Tiron solution was found to be two per metal ion, and the stability constant of the ML complex was found to be log β 1 ) 14.11. 2 As the constant was always found to be 3 for higher molar ratios, the stability constant was found to be log β 2 ) 43.97 considering the presence of the M 2 L 3 dinuclear complex in the medium. It was reported that in the Y(III)-Tiron system Tiron bound to Y(III) by both phenolic hydroxyls and that a five-membered chelate ring was formed.…”
Section: Formation Constants Of the Y(iii) Complexesmentioning
confidence: 90%
See 2 more Smart Citations
“…Occasionally, parts of them are synthesized by single organic ligands containing both N- and O-donor atoms, such as imidazole–dicarboxylic acid or pyridine–dicarboxylic acid . Furthermore, in order to meet the high-coordination-number requirement of lanthanide ions and construct novel structural topologies, a lot of mixed organic ligands with N- or O-donor atoms can also be employed in construction of Zn–Ln MOFs …”
Section: Introductionmentioning
confidence: 99%